2015
DOI: 10.4238/2015.january.15.8
|View full text |Cite
|
Sign up to set email alerts
|

Association of PTPN22 gene polymorphism with type 1 diabetes mellitus in Chinese children and adolescents

Abstract: ABSTRACT. Previous studies have indicated that the protein tyrosine phosphatase nonreceptor type 22 gene (PTPN22) is associated with type 1 diabetes (T1DM) in the Caucasian population. In the present study, we investigated the relationship between PTPN22 genetic polymorphisms and T1DM in Chinese children. A total of 202 children and adolescents with T1DM and 240 healthy control subjects of Chinese Han origin were included in our analysis. Polymerase chain reaction-restriction fragment length polymorphism was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…Regarding the association between gender, age of onset of T1D, type of presentation, and PTPN22 C1858T in T1D patients, in our study, there was statistically insignificant difference between PTPN22 genotypes (TT, TC, and CC) and the above mentioned parameters (P > 0.05); these results agreed with some studies [26,28]. On the other hand, they were in disagreement with others who found gender differentiation in favor of females [27,30].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Regarding the association between gender, age of onset of T1D, type of presentation, and PTPN22 C1858T in T1D patients, in our study, there was statistically insignificant difference between PTPN22 genotypes (TT, TC, and CC) and the above mentioned parameters (P > 0.05); these results agreed with some studies [26,28]. On the other hand, they were in disagreement with others who found gender differentiation in favor of females [27,30].…”
Section: Discussionsupporting
confidence: 67%
“…Our genotypic results were in agreement with Bottini et al [13], who firstly reported an association between the PTPN22 polymorphism and T1D from North America and Sardinia. On the frame of the necessity of throughout additional research to clarify the varied geographic distribution, recent several studies involved different populations had explored the relationship between PTPN22 and T1M including those from Italy [14,15], Spain [16], Denmark [17], Finland [18], Brazil [19], France [20], Germany [21,22], the UK [23], Poland [24], Greece [25], China [26], and Egypt [27]. On the contrary, other studies were reported which denied the association between 1858C/T polymorphism and susceptibility to T1D [28,29].…”
Section: Discussionmentioning
confidence: 99%
“… 80 The association of SNPs in PTPN22 with T1DM also differentiates between populations of different ethnicity, such as Chinese and Japanese. 81 84 These differences may be due to the role of PTPN22 only as a supplementary risk factor to AITD and T1DM, or due to different additional risk factors such as age and gender. 79 , 85 Recent research has revealed how age has a great effect on the clinical pattern of diseases; with HT and other autoimmune diseases, clustering can occur at different life stages.…”
Section: Genetics and Autoimmunitymentioning
confidence: 99%
“…74 Bottini et al (2004);75 Velaga et al (2004);76 Bulut et al (2014);77 Smyth et al (2004);78 Lee et al (2011);79 Alkhateeb et al (2013);80 Liu et al (2015);81 Ikegami et al (2006); 82 El Fotoh et al (2019); 83 Giza et al (2013); 84 Wasniewska et al (2012); 85 Prezioso et al (2017); 86 Burn et al (2011); 87 Blasetti et al (Ban et al (2007); 94 Inoue et al (2010); 95 Villano et al (2009); 96 Li et al (2015); 97 Bossowski et al(2013); 98 Nakano et al (2007); 99 Korn et al (2009); 100 Li et al (2016); 101 Bjornvold et al (2006); 102 Rubio-Cabezas et al (2009); 103 Zavattari et al (2004); 104 Nakanishi and Shima (2007); 105 Brusko et al (2007); 106 Tritt et al (2008); 107 Brode et al (2006); 108 Tian et al (2009); 109 Jaeckel et al (2005); 110 Peng et al (2004); 111 Wu et al (2012); 112 Zheng et al (2009); 113 Johnson et al (2013) 114 Golden et al (2005); 43 Villano et al (2009); 96 Chen et al (2013); 121 Pastuszak-Lewandoska et al (2012); 122 Douroudis et al (2009); 123 Bednarczuk et al (2003); 124 Hou et al (2015); 125 Vaidya et al (1999); 126 Kavvoura et al (2007); 127 Lee et al (2000); 128 Ikegami et al (2006); 129 Mochizuki et al (2003); 130 Howson et al (2007); 131 Tang et al (2012); 132 Takara et al (2000); 133 Mayans et al (2007); 134 Balic et al (2009); 135 Ban et al (2001); 136 Celmeli et al (2013);137 Chen and Li (2019);138 Wang et al (2017); 139 Kavvoura et al (2005); 140 Liu et al (2013); 141 Dong et al (2014); 142 Fathima et al (2019); 143 Bicek et al (2009); 144 Einarsdottir et al (2003);146 Ban and Tomer (2003);147 Aversa et al148 (2019); Orban et al (2011); 149 Orban et al (2014)150 Abatacept AIRE, autoimmune regulator; AITD, thyroid autoimmune disease; CTLA-4, cytotoxic T lymphocyte-associated antigen-4; FOXP3, forkhead box protein P3; HLA, human leukocyte antigen; LYP, lymphoid protein tyrosine phosphatase; T1DM, type 1 diabetes mellitus.…”
mentioning
confidence: 99%
“…Also, some previous studies reported a lack of this variant in Asians (mainly from China and South Asia) [ 27 28 ]. A more recent report from China however, did find an association between the PTPN22 gene and T1DM [ 53 ]. In Egyptian T1DM patients, the TT genotype was detected in only 2% patients [ 54 ].…”
Section: Discussionmentioning
confidence: 99%